Continuity, change, and contradictions: risk and agency in criminal careers to age 59 - Sivertsson, Fredrik (Criminal justice and behavior, 2015)
This study's point of departure is the current debate over the ability to make prospective long-term predictions of criminal offending based on childhood risk factors. We begin by constructing groups based on cumulative childhood risk and measure their subsequent criminal career outcomes. The results show clear differences in adult offending but also considerable heterogeneity, suggesting that the relationship between risk factors and individuals' subsequent offending or non-offending is complex and in need of closer study. We therefore identify individuals in the low- and high-risk groups who did not develop the criminal careers that could be expected from their risk scores and, using deviant case analysis, qualitatively analyze their life histories. Together, these cases inform us of the importance of the dynamics of risk, human agency, and the life course, as well as the historical influences under which their lives unfolded?features of social life that could in no way be predicted prospectively.